An Empirical Investigation of the Impact of Service Quality Dimensions on Guests Satisfaction: A Case Study of Dubai Hotels - MOUZAEK, ELENA; MARZOUQI, AMINA AL; ALAALI, NADER; SALLOUM, SAID A.; ABURAYYA, AHMAD; SUSON, ROBERTO (The journal of contemporary issues in business and government, 2021)
Customers' satisfaction is one of the most important indicators to identify the hotel sector's service quality level. The study's main purpose was to measure the impact of service quality dimensions on customer satisfaction in the hotel industry in the United Arab Emirates. In particular, this study examines why service quality is a critical determinant of the hotel sector's organisational performance. The study used quantitative methods to achieve the objectives of the research. A self-administered questionnaire was designed to collect the data using the drop-off technique. The questionnaires were distributed to 5000 in-house customers (domestic and international) at the hotels. In total, 3748 customer questionnaires were used in the study, yielding a 75% response rate. In this study, hypotheses were tested through the multiple regression model using SPSS 25.00. Multiple regression analysis showed that tangibles,responsiveness and empathy have significant positive effects on customer satisfaction (=.120,P<0.05;=.173,P<0.05;= .495, ρ < 0.01, respectively). The study found that service quality helped organisations meet customers' needs and expectations and enhanced satisfaction. Organisations could, therefore, achieve improved financial performance by offering excellent quality services that meet customer needs and expectations. Therefore, improving hotel service quality could result in higher satisfaction levels of hotel customers.